Determination of Submillimeter Atmospheric Opacity at El Leoncito, Argentina Andes - Melo, Arline M. (2003)
We present submillimeter wave atmospheric opacity determinations obtained at 212 GHz and 405 GHz for the site of El Leoncito, San Juan, Argentina Andes, located at an altitude of 2550 meters, using the Solar Submillimeter wave Telescope (SST). The use of SST allowed the comparison of three different methods of measurements: (a) indirect derivation from the sky brightness temperature variation with the elevation angle; (b) directly derived from solar signal attenuation with elevation angle; and (c) use of the product of solar brightness times the antenna coupling factor, as the reference source external to the atmosphere. It has been shown that the last method provides the most consistent measurements for the two frequencies. Preliminary results show that opacities (in nepers) for El Leoncito at 405 GHz are 5.5 times larger than at 212 GHz, smaller than model predictions, which suggest smaller opacities for shorter submm-waves at that site. Preliminary survey for 1999-2001 at El Leoncito indicate most probable values for zenith opacities of 0.18 nepers (212 GHz) and 0.9 nepers (405 GHz), which are comparable to a number of other sites at considerably higher altitudes.